2011
DOI: 10.1016/j.freeradbiomed.2011.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Omeprazole attenuates hyperoxic injury in H441 cells via the aryl hydrocarbon receptor

Abstract: Hyperoxia contributes to the development of bronchopulmonary dysplasia in premature infants. Earlier we observed that aryl hydrocarbon receptor (AhR)-deficient mice are more susceptible to hyperoxic lung injury than AhR-sufficient mice, and this phenomenon was associated with a lack of expression of cytochrome P450 1A enzymes. Omeprazole, a proton pump inhibitor, used in humans with gastric acid related disorders, activates AhR in hepatocytes in vitro. However, the effects of omeprazole on AhR activation in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
38
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 47 publications
3
38
1
1
Order By: Relevance
“…Furthermore, recent studies have demonstrated an attenuating effect of CYP1A1 inducers on hyperoxic lung injury both in vitro [10,24] as well as in vivo [11][12][13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, recent studies have demonstrated an attenuating effect of CYP1A1 inducers on hyperoxic lung injury both in vitro [10,24] as well as in vivo [11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…Transplacental transfer is present but low, and dependent on the maternal plasma levels [23]. To our knowledge the use of omeprazole in preventing hyperoxia induced lung injury has only been demonstrated so far in vitro [24] and in in vivo mice models [12,25]. Herein, we test the hypothesis that in a hyperoxic induced lung injury preterm rabbit model, prenatal or neonatal administration of omeprazole (1) induces transcription of CYP1A1 in a dose-dependent way and (2) improves pulmonary outcome both on histological as well as functional level.…”
mentioning
confidence: 97%
“…In tumors in human, overexpression of COX-2 leads to an increase in prostaglandin (PG) levels which affects many mechanisms involved in carcinogenesis, such as angiogenesis, inhibition of apoptosis, and stimulation of cell growth, as well as invasiveness and the metastatic potential of tumor cells (Cervello and Montalto, 2006). Several reports suggest that OPZ might have an anti-inflammation effect (Kedika et al, 2009;Shivanna et al, 2011). Indeed, OPZ inhibited ROS production and protected against oxidative stress by inducing heme-oxygenase-1 (Kedika et al, 2009;Shivanna et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Several reports suggest that OPZ might have an anti-inflammation effect (Kedika et al, 2009;Shivanna et al, 2011). Indeed, OPZ inhibited ROS production and protected against oxidative stress by inducing heme-oxygenase-1 (Kedika et al, 2009;Shivanna et al, 2011). However, the ligands of AhR, including TCDD and B[a]P, induced Cox-2 expression (Degner et al, 2007 and.…”
Section: Discussionmentioning
confidence: 99%
“…Total mRNA was isolated and reverse transcribed to cDNA as mentioned before (Shivanna et al, 2011a). Real-time quantitative reverse-transcription polymerase chain reaction analysis was performed with the 7900HT Real-Time PCR System using iTaq Universal SYBR Green Supermix (1725121; Bio-Rad).…”
Section: Methodsmentioning
confidence: 99%